Case report: Acute HHV6B encephalitis/myelitis post CAR-T cell therapy in patients with relapsed/refractory aggressive B-cell lymphoma - Li, Ningwen; Zhang, Ruoxuan; Wang, Jue; Zhu, Xiaojian; Meng, Fankai; Cao, Yang; Wang, Gaoxiang; Yang, Yang (Frontiers in Neurology, 2024)
The development of chimeric antigen receptor (CAR)-T cell therapy has revolutionized treatment outcomes in patients with lymphoid malignancies. However, several studies have reported a relatively high rate of infection in adult patients following CD19-targeting CAR T-cell therapy, particularly in the first 28 days. Notably, acute human herpesvirus 6 B (HHV6B) reactivation occurs in up to two-thirds of allogeneic hematopoietic stem cell transplantation patients. Case presentations: Herein, we describe a report of HHV6B encephalitis/myelitis in three patients with relapsed/refractory diffuse large B-cell lymphoma post CAR T-cell therapy. All three patients received multiple lines of prior treatment (range: 2-9 lines). All patients presented with fever that persisted for at least two weeks after CAR-T cell infusion (CTI). Both the onset time and duration were similar to those of the cytokine release syndrome (CRS); nevertheless, the CRS grades of the patients were low (grade 1 or 2). Delirium and memory loss after CTI were the earliest notable mental presentations. Neurological manifestations progressed rapidly, with patients experiencing varying degrees of impaired consciousness, seizures, and coma. Back pain, lumbago, lower limb weakness and uroschesis were also observed in Patient 3, indicating myelitis. High HHV6B loads were detected in all Cerebral spinal fluid (CSF) samples using metagenomic next-generation sequencing (mNGS), implying its reliability in detecting HHV6B infections in the CNS. Only one patient required high-activity antivirals and IgG intravenous pulse treatment finally recovered, whereas the other two patients died from HHV6B encephalitis. Conclusions: Considering its fatal potential, HHV6B encephalitis/myelitis should be urgently diagnosed post CAR-T cell-based therapy. Furthermore, hematologists should differentially diagnose these conditions from CRS or other immunotherapy-related neurotoxicities as early as possible. The results of this study demonstrate the potential of mNGS in the early diagnosis of HHV6B infection, particularly when the organism is difficult to culture.